Heteropogon‐Themeda grasses evolve to occupy either tropical grassland or wetland biomes. Issue 3 (23rd May 2022) - Arthan, Watchara; Morales‐Fierro, Vanezza; Vorontsova, Maria S.; Kellogg, Elizabeth A.; Mitchley, Jonathan; Lehmann, Caroline E. R.
Abstract: Species of the Heteropogon ‐ Themeda clade are ecologically important grasses distributed across the tropics, including widespread species, such as the pantropical Heteropogon contortus and Themeda triandra, and range‐restricted species such as Heteropogon ritchiei and Themeda anathera . Here, we examine habitat preferences of the grassland/savanna and wetland species by describing bioclimatic niche characteristics, characterizing functional traits, and investigating the evolution of functional traits of 31 species in the Heteropogon ‐ Themeda clade in relation to precipitation and temperature. The climatic limits of the clade are linked to mean annual precipitation and seasonality that also distinguish seven wetland species from 24 grassland/savanna species. Tests of niche equivalency highlighted the unique bioclimatic niche of the wetland species. However, climatic factors do not fully explain species geographic range, and other factors are likely to contribute to their distribution ranges. Trait analyses demonstrated that the wetland and grassland/savanna species were separated by culm height, leaf length, leaf area, awn length, and awn types. Phylogenetic analyses showed that the wetland species had tall stature with long and large leaves and lack of hygroscopic awns, which suggest selective pressures in the shift between savanna/grassland and wetland. The two most widespread species, H. contortus and T. triandra, have significantly different bioclimatic niches, but we also found that climatic niche alone does not explain the current geographic distributions of H. contortus and T. triandra . Our study provides a new understanding of the biogeography and evolutionary history of an ecologically important clade of C4 tropical grasses.